Overview of the institutional and normative-legal framework for anti-corruption policy in Ukraine - Tkachenko, Andrii (Public Policy and Accounting, 2024)
The article examines the transformation of Ukraine’s anti-corruption policy following the 2014 Revolution of Dignity in the context of European integration. It outlines the main stages in the development of the modern anti-corruption infrastructure, including the establishment of specialized institutions — NABU, NACP, SAPO, HACC, ARMA, and the SBI. The legal framework is analyzed, including the laws «On Prevention of Corruption», «On the National Anti-Corruption Bureau of Ukraine», «On the High Anti-Corruption Court», as well as amendments regarding the protection of whistleblowers. The article highlights the role of the Anti-Corruption Strategy for 2021–2025 and the State Anti-Corruption Program as instruments for implementing systematic state policy. Emphasis is placed on mechanisms for preventing corruption: electronic asset declarations, transparent public procurement via the ProZorro system, conflict of interest regulation, digitalization of public services, and public awareness campaigns. It is noted that despite the establishment of institutional and legislative foundations, the main challenge remains effective law enforcement, particularly regarding the independence of anti-corruption bodies and the judiciary. The article analyzes the influence of international organizations (EU, IMF, OECD) on shaping Ukraine’s anti-corruption policy and evaluates the implementation of international conventions. It also explores the prospects for further development of the system, considering the challenges of wartime and the requirements of EU integration. Based on the findings, the article provides recommendations for strengthening inter-agency coordination, improving digital oversight tools, and fostering a culture of integrity in society.